Organic–inorganic hybrid nanomaterials based on inorganic oxides and a mesomorphic polyazomethine. (August 2015) - Perju, Elena; Ghimpu, Lidia; Hitruc, Gabriela; Harabagiu, Valeria; Bruma, Maria; Marin, Luminita
Organic–inorganic hybrid materials have been obtained by impregnating a mesomorphic polyazomethine into a porous inorganic matrix of zinc oxide (ZnO), tin dioxide (SnO2 ), or mixed ZnO/SnO2 . The porous inorganic matrix has been obtained by magnetron sputtering technique and proved a very high crystallinity degree. The resulting hybrid materials were characterized from morphological and optical points of view by scanning electron microscopy, atomic force microscopy, and ultraviolet-visible and photoluminescence spectroscopy. The inorganic matrix itself exhibited a highly rough surface, which became smoother after polymer impregnation, indicating its complete coverage. The violet emission of the separate inorganic and organic components turned into a blue and green light emission, respectively, of the hybrid materials, suggesting the possibility to modulate the color of emitted light by the simple choice of the inorganic matrix. Considerations with regard of interface phenomena that prompted the photophysical changes of the hybrid materials were done.